Intersectional Inequities in Age-Related Risk of Adverse Maternal Cardiometabolic Health - Elleni M. Hailu; Mahasin S. Mujahid; Safyer Mckenzie-Sampson; Audrey Lyndon; Suzan L. Carmichael (JAMA Cardiology, 2026)
Importance Compared with White women, Black women are at increased risk of adverse perinatal cardiovascular conditions—leading causes of maternal mortality. Yet little is known about how age-related physiologic decline, ie, weathering , together with intersecting sources of social adversity shape these disparities. Objective To quantify differential age-related perinatal cardiometabolic risk at the intersection of race and ethnicity and socioeconomic status (SES). Design, Setting, and Participants This cross-sectional study used statewide hospital discharge data from California between 2007 and 2019 of all births (live and stillbirths) occurring at greater than or equal to 20 weeks’ gestation among Black and White women. Analyses were performed between October 2024 to September 2025. Exposures Self-reported maternal race and ethnicity, age, education, and insurance type. Main Outcomes and Measures Hypertensive disorders of pregnancy (HDP; chronic hypertension, gestational hypertension or preeclampsia, or eclampsia) and its subtypes were evaluated. Nonoptimal cardiovascular health before and during pregnancy was also assessed using a metric evaluating hypertension, diabetes, smoking, body mass index, and gestational weight-gain adjusted for gestational age. Modified Poisson regression models with robust SEs, adjusting for pregnancy-related characteristics and year fixed effects were used to determine risk associated with increases in age across combinations of race and ethnicity and SES (education or insurance), and to estimate the corresponding average predicted probabilities. Results This study included 1 880 400 births (mean [SD] maternal age, 29.9 [5.9] years). Across all SES categories, increases in age-related risk of adverse outcomes were higher among Black women compared with White women in similar or more deprived SES strata. Risk increases were most pronounced among Black women with the lowest SES. Disparities at the intersection of race and SES widened with age. Moreover, Black women with higher SES had more pronounced or equivalent age-related risk as White women with lower SES. For example, among college-educated Black women, each 5-year increase in age was associated with a 27% higher risk of HDP (95% CI, 1.24-1.29), whereas among White women with a high school degree or less, a similar increase in age was associated with a 23% higher risk (95% CI, 1.22-1.24). Conclusions and Relevance Findings of this cross-sectional study highlight the need to address structural drivers and chronic stressors earlier in the life course to eliminate disparities in maternal cardiovascular health.